2023
DOI: 10.3390/ijerph20126061
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiopulmonary Response of High-Intensity Interval Training with Elastic Resistance vs. High-Intensity Interval Training on a Treadmill in Healthy Adults

Abstract: This study aims to describe and compare cardiopulmonary and subjective responses during high-intensity interval training with elastic resistance (EL-HIIT) and traditional high-intensity interval training (HIIT) sessions. Twenty-two healthy adults (27.6 ± 4.4 years) performed an EL-HIIT and a HIIT protocol consisting of 10 × 1 min at ~85% V·O2max prescribed by cardiopulmonary-specific tests. Pulmonary parameters, heart rate (HR), blood lactate, and rate of perceived exertion (RPE) were measured during exercise.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To calculate body fat percentage (% BF), skinfold thicknesses (SFTs) were used and it was computed via gender-specific formulae. 9…”
Section: Methodsmentioning
confidence: 99%
“…To calculate body fat percentage (% BF), skinfold thicknesses (SFTs) were used and it was computed via gender-specific formulae. 9…”
Section: Methodsmentioning
confidence: 99%
“…Heart rate was monitored throughout the session using a heart rate monitor. The exercise series lasted one minute, performed at an intensity equivalent to VT2 determined by CPX-EL (Stage 6), with a passive interval of one minute between series, protocol 10 x 60s:60s [19]. The volunteer was encouraged to follow the rhythm emitted by a metronome (Cellphone Application -®Cifraclub).…”
Section: Training Program -El-hiitmentioning
confidence: 99%
“…A novel and cost--effective alternative is Elastic Resistance High-Intensity Interval Training (EL-HIIT), which can be performed in diverse spaces. Recent studies using interval exercise with elastic resistance have demonstrated essential reductions in blood pressure and blood glucose after exercise [17,18] and has the potential for developing cardiorespiratory fitness [19]. Gasparini-Neto et al [17] demonstrated that an interval exercise session with elastic resistance reduced blood pressure and blood glucose in older women with and without hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…This study focused on two types of endurance training: moderate-intensity continuous training (MICT) and High-intensity interval training (HIIT). The continual method is primarily used for the development of aerobic endurance during a continual strain of a cyclic character, otherwise known as a periodic exercise that lasts for a longer period (Máček et al, 2011). As a study by Novotný et al (2008) states, aerobic training with a continuous load and low intensity is longterm slow movement training over a longer distance (Novotný, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The continual method is primarily used for the development of aerobic endurance during a continual strain of a cyclic character, otherwise known as a periodic exercise that lasts for a longer period (Máček et al, 2011). As a study by Novotný et al (2008) states, aerobic training with a continuous load and low intensity is longterm slow movement training over a longer distance (Novotný, 2008). On the other hand, interval methods alternate between intervals of load and rest.…”
Section: Introductionmentioning
confidence: 99%